Characteristics of Vata and its association with Nervous system (Bheshaja: Journal of Central Ayurveda Campus, 2025)
Ayurveda, the science of life is all about preserving health and curing disease through the understanding of bodily principles, especially the Tridosha. Among them, Vata Dosha is regarded as the most important, which controls all physiological functions as well as perception, movement, and communication. Through the lens of contemporary biomedical science, this review seeks to examine the characteristics, locations, functions, and subtypes of Vata as well as its relationship to the neurological system. Ayurveda introduces Vata as the force of life that rules all the movements and sensory activities of the body. It is described by its qualities such as Amurtatva (formlessness), Anavasthita (instability), Chalatva (mobility) and can only be perceived by its action. Vata moves and functions through the Vatavaha Srotas, which are functionally analogous to neural pathways. These are categorized as Sangyavaha (sensory) and Chestavaha (motor) Srotas (channels), and they are further separated into Samvrita (myelinated) and Asamvrita (demyelinated) structures. This aligns closely with the central and peripheral nervous systems. In the same way the five subtypes of Vata; Prana, Udana, Samana, Vyana, and Apana govern key physiological functions that correspond to neurological, autonomic, and visceral processes. This integrative review concludes that the conceptual and functional framework of Vata Dosha closely mirrors the structure and role of the nervous system in contemporary medicine. Such cross-system comparison enhances the understanding of neuro-physiological processes through Ayurvedic principles and provides a basis for further research into Vata-related disorders (Vatavyadhi) as possible Ayurvedic representations of neurological diseases.